Assessment of Deforestation (2000-2020) in Peruvian Forest Concessions in the Province of Tambopata (Madre de Dios) Using Open Data Platforms - Valle-Basto, Daniel Fernando (2023)
The data obtained through the EarthMap platform are comparable to those from Geobosques platform (Peru) for the same period 2000-2020. Thus, based on the use of these platforms, it was possible to estimate that the forest concessions in the province of Tambopata (Madre de Dios) have Lost 32,115.36 hectares of forest cover, representing 20.96% of all deforestation in the region. During the same period, Peru's forestry legislation was changed up to three times. These changes have not allowed the implementation of long-term strategies focused on true sustainable forest management, as well as the control and reduction of Amazon deforestation. It was also observed that reforestation concessions, ecotourism concessions, and concessions for the use of non-timber products, are first used for logging purposes, and then they are converted for other land uses, such as agricultural fields or livestock management. or mining extraction. Under these legal and institutional conditions of forest management in Madre de Dios, forest units and concessions do not provide guarantees to prevent deforestation.